Empowering Speaking Achievement by Using Inside-Outside Fishbowl - Ridha Ilma; Jenny Elvinna Manurung (Channing : Journal of English Language Education and Literature, 2019)
This study aimed to describe the implication of speaking achievement by applying inside-outside fishbowl (IOF) to the students of Tridinanti University Palembang. The total number of samples was seventeen of sixth-semester students of the English study program of Tridinanti University Palembang, they were selected by using purposive sampling. This study used classroom action research. It consisted of two cycles; cycle I and cycle II. Speaking tests and observations were used to collect the data. It was found that there was a significant improvement in students' speaking achievement, the mean score of speaking achievement in cycle I was 64.47, and there was only 29.41% of the students who achieved predetermined minimum standard mastery. Based on the finding on cycle I, the writers needed to improve the students’ speaking achievement by conducting cycle II. After did cycle II, the mean score of speaking achievement was 79.76, and there was 94.11% of the students who achieved predetermined minimum standard mastery. This strategy builds the students’ participation in doing discussion and helps them reflect on what a good discussion looks like. Using Inside-Outside Fishbowl (IOF) in EFL classrooms has helped both lecturers and learners in many different ways. It has a positive impact on both of them. Regarding students, IOF application in the classroom has helped them to think and organize their thoughts. As a result, they have started to manage their learning and to gain a sense of responsibility. Moreover, they have shown readiness to speak in the target language with more confidence and fluency. Students have begun to have opportunities so they can show how good they are in speaking and sharing ideas.